IMF Research Bulletin, December 2016. (IMF Research Bulletin; IMF Research Bulletin, 2016)
The Research Summaries in this issue of the IMF Research Bulletin cover 'Tax Capacity and Growth' (by Vitor Gaspar, Laura Jaramillo, and Philippe Wingender), and 'U.S. Shale Revolution and Its Spillover Effects on the Global Economy' (Ravi Balakrishnan, Keiko Honjo, Akito Matsumoto, and Andrea Pescatori). The Q and A coauthored by Amadou Sy and Mariama Sow covers 'Seven Questions about the Relationship between Country Finance and Governance.' A listing of recent IMF Working Papers, Staff Discussion Notes, and Recommended Readings from IMF Publications is included in the IMF Research Bulletin. Readers can also find news on free-to-view articles from IMF Economic Review and a call for conference papers in this issue of the Bulletin.